2014
DOI: 10.1016/j.jmbbm.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A robust anisotropic hyperelastic formulation for the modelling of soft tissue

Abstract: The Holzapfel-Gasser-Ogden (HGO) model for anisotropic hyperelastic behaviour of collagen fibre reinforced materials was initially developed to describe the elastic properties of arterial tissue, but is now used extensively for modelling a variety of soft biological tissues. Such materials can be regarded as incompressible, and when the incompressibility condition is adopted the strain energy Ψ of the HGO model is a function of one isotropic and two anisotropic deformation invariants. A compressible form (HGO-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(120 citation statements)
references
References 27 publications
(38 reference statements)
1
119
0
Order By: Relevance
“…We obtain the syntax for Neo-Hookean model from [18]; further we confirmed that our UMAT code is correct by comparing with the formulation in [19] for the same Holzapfel (MA) model.…”
Section: Implementation Of the Holzapfel Modelsupporting
confidence: 63%
“…We obtain the syntax for Neo-Hookean model from [18]; further we confirmed that our UMAT code is correct by comparing with the formulation in [19] for the same Holzapfel (MA) model.…”
Section: Implementation Of the Holzapfel Modelsupporting
confidence: 63%
“…To consider compressible deformation, the HGO-C model was suggested, with the anisotropic part expressed by isochoric invariants (insensitive to volumetric deformation). However, Nolan et al [26] found that the HGO-C model was unable to simulate compressible anisotropic behavior correctly, because it used isochoric anisotropic invariants which is insensitive to volumetric deformation. Consequently, they formulated a modified anisotropic (MA) model by using the full anisotropic invariants which accounted for a volumetric anisotropic contribution.…”
Section: Materials Modelmentioning
confidence: 99%
“…Several studies, e.g., Helfenstein et al [14], Annaidh et al [1] and Nolan et al [22], have reported the erroneous analysis results of fiber-reinforced anisotropic material models for soft biological tissues (Weiss et al [37], Holzapfel et al [16] and Rubin and Bodner [25]) when they are mistakenly used in the compressible domain; e.g., a sphere reinforced with one family of fibers would be deformed into a sphere with a smaller size upon hydrostatic pressure instead of taking on an ellipsoidal shape. One remedy for (ii) is to implement the computationally (rather) expensive augmented Lagrangian method to bring the analysis towards the incompressibility limit, see Glowinski and Le Tallec [8,9] and Simo and Taylor [31] among others.…”
Section: Introductionmentioning
confidence: 99%